2015
DOI: 10.1002/2015gl064596
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of Atlantic Meridional Overturning Circulation Fingerprint and implications for decadal predictability in the North Atlantic

Abstract: It has been suggested previously that the Atlantic Meridional Overturning Circulation (AMOC) anomaly associated with changes in the North Atlantic Deep Water formation propagates southward with an advection speed north of 34°N. In this study, using Geophysical Fluid Dynamics Laboratory Coupled Model version 2.1 (GFDL CM2.1), we show that this slow southward propagation of the AMOC anomaly is crucial for the evolution and the enhanced decadal predictability of the AMOC fingerprint—the leading mode of upper ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
97
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 39 publications
20
97
0
Order By: Relevance
“…S6 in the supplemental material). The positive AMOC anomaly subsequently extends southward; at 308N, the AMOC experiences a maximum another 2-3 years later (not shown), consistent with Zhang (2010) and Zhang and Zhang (2015). The AMOC anomaly associated with the AMV is shown in Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…S6 in the supplemental material). The positive AMOC anomaly subsequently extends southward; at 308N, the AMOC experiences a maximum another 2-3 years later (not shown), consistent with Zhang (2010) and Zhang and Zhang (2015). The AMOC anomaly associated with the AMV is shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…The anomalies are reversed during cold phases (cold subpolar gyre, warm Gulf Stream), consistent with our findings. Furthermore, this pattern of subsurface heat content has been identified as a ''subsurface fingerprint of the AMOC'' by Zhang (2008), who attributed it to meridional heat transport convergence in the subpolar gyre associated with an increased AMOC and associated heat transport divergence in the Gulf Stream region (see also Zhang and Zhang 2015).…”
mentioning
confidence: 99%
“…In the subpolar North Atlantic a freshening and cooling has occurred after 2005 (Robson et al, 2016;Tesdal et al, 2018), which is suggested to have been induced by negative density anomalies resulting from the post-1995 decadal subpolar gyre warming (Häkkinen & Rhines, 2004;Hátún et al, 2005;Robson et al, 2014). Here, the freshwater input is not a locally generated feature, but a signature of decadal overturning circulation variability in the North Atlantic (Smeed et al, 2018;Zhang, 2008;Zhang & Zhang, 2015). Measurements on Nuka Arctica confirm a substantial winter cooling from 2004 to 2017 and simultaneously a freshening in the Iceland Basin.…”
Section: Resultsmentioning
confidence: 75%
“…This might be associated with the existence of interior Atlantic Meridional Overturning Circulation (AMOC) pathways. A stronger (weaker) AMOC results in warming (cooling) in the subpolar gyre after several years, contributing to enhanced decadal predictability of sea ice in the North Atlantic sector (e.g., Mahajan et al, 2011;Zhang and Zhang, 2015). In contrast to September, the analysis of March regional indices suggests that sea ice in the Atlantic side has higher predictability than that of the Pacific side.…”
Section: Discussionmentioning
confidence: 99%